Pallidal neuron activity determines responsiveness to deep brain stimulation in cervical dystonia. Issue 12 (December 2021) - Sedov, Alexey; Popov, Valentin; Gamaleya, Anna; Semenova, Ulia; Tomskiy, Alexey; Jinnah, Hyder A.; Shaikh, Aasef G.
Highlights: Pallidal single-neuron discharges are abnormal in dystonia. Neurons have different isolated discharge pattern at deep brain stimulation responsive pallidal regions. The differences in deep brain stimulation responsive regions are also evident in local field potentials. Abstract: Objective: In patients with cervical dystonia we sought for the differences in neuronal behavior of pallidal regions where deep brain stimulation resulted in favorable therapeutic response compared to those where the response was absent. Methods: We compared single-unit activity of 564 neurons recorded from deep brain stimulation sensitive and non-sensitive regions in 17 cervical dystonia patients. Results: Globus pallidus internus regions responsive to the deep brain stimulation had lower firing rates and bursting compared to non-responsive areas. The differences were robust in locations where neuronal responses correlated with neck movements. Per the effects of deep brain stimulation, the pallidal regions were classified in weak, intermediate, and excellent responsive. Pallidal regions with weak response to deep brain stimulation had fewer burst neurons and higher firing rate compared to neurons in areas with excellent response. The burst index was significantly decreased in excellent response regions. There was a significant decrease in the alpha band oscillation score but a substantial increase in the gamma band in excellent response neurons. Conclusion: The pallidal region that would be responsive to deep brain stimulation has distinct physiology compared to the non-responsive region. Significance: These results provide novel insights into globus pallidus interna neurons' physiology in cervical dystonia.